Pengaruh Lingkungan Belajar Terhadap Konsentrasi Belajar Mahasiswa Sekolah Tinggi Teologi EFATA - Mohammad Alvin Evriantara (Peneliti.net, 2022)
This study aims to determine whether and how much significant the influence between the variables of learning environment and learning concentration on EFATA theological high school students is. The type of research in this study is quantitative with correlational research methods, namely the type of research is research using statistical methods that aim at measuring two or more variables. In this study, we want to know how much influence the learning environment has on the learning concentration of EFATA high school students. The population in this study were 49 students of the EFATA theological high school. Sampling in this study applied the total population sampling technique, that is, all populations were used as research samples. Therefore this research is included in population research. Collecting data in this study using questionnaires. The analysis and data used a simple linear regression technique using SPSS version 25. The results showed a significance with a significance value of 0.000 <0.05 on the learning environment variable on learning concentration. So that the influence of the learning environment on the learning concentration of EFATA theological high school students obtains an influence level of 62% while for 38% is the influence of other factors.